2016
DOI: 10.1016/j.cmet.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Immunity-Based Evolutionary Interpretation of Diet-Induced Thermogenesis

Abstract: Diet-induced thermogenesis (DIT) has often been argued to be a physiological defense against obesity, but no empirical proof of its effectiveness in limiting human body weight gain is available. We here propose an immune explanation of DIT-i.e., that it results from the coevolution of host and gut microbiota (especially Firmicutes) that ferment ingested food and proliferate, causing periodic, vagally mediated increases in thermogenesis aimed at curtailing their expansion. Because of this evolutionary adaptive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 116 publications
0
6
0
1
Order By: Relevance
“…The levels of UCP1were higher in mice treated with HFD. This phenomenon might be explained by diet-induced thermogenesis (DIT) 40,41 .We proffer that HFD stimulated thermogenesis in brown adipose tissue (BAT), and the mice displayed elevated BAT activity. Further study is needed to explore and verify this mechanism, however.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of UCP1were higher in mice treated with HFD. This phenomenon might be explained by diet-induced thermogenesis (DIT) 40,41 .We proffer that HFD stimulated thermogenesis in brown adipose tissue (BAT), and the mice displayed elevated BAT activity. Further study is needed to explore and verify this mechanism, however.…”
Section: Discussionmentioning
confidence: 99%
“…Vagal afferents have been proposed to serve as a relay between the GI microbiome and brain functions [83] , [84] , presumably in response to the activation of vagal afferents by microbial metabolites. The fact that peripheral sensory neurons reside outside the blood–brain barrier makes them a particularly relevant target for pharmacological agents mimicking metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…Firmicutes and bacteroidetes are considered especially important to public health. Firmicutes can ferment ingested food, while Bacteroidetes uptake and degrade polysaccharides (Xu et al, 2003;Liao et al, 2016). Turnbaugh et al (2006) found that after transplanting obese germfree mice with a relative high profusion of Firmicutes and nonobese mouse gut microbiota with a higher relative abundance of Bacteroides, the obese microbiome recipient mice had a higher dietary energy harvesting ability.…”
Section: Discussionmentioning
confidence: 99%
“…Firmicutes and bacteroidetes are considered especially important to public health. Firmicutes can ferment ingested food, while Bacteroidetes uptake and degrade polysaccharides ( Xu et al., 2003 ; Liao et al., 2016 ). Turnbaugh et al.…”
Section: Discussionmentioning
confidence: 99%